PERANAN BADAN KEPEGAWAIAN DAERAH DALAM PELAKSANAAN REKRUTMEN PEGAWAI NEGERI SIPIL (STUDI PEMERINTAHAN KABUPATEN PROBOLINGGO) - Ainul Yaqin (SOCIAL EDU: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of this research is to explain the role of the Regional Civil Service Agency (BKD) in the recruitment process of Civil Service Candidates (CPNS) within the Probolinggo Regency Government. The type of research used is a descriptive-qualitative approach, which aims to describe the answers to the issues regarding the role of the BKD in recruitment. The data collected are processed and analyzed descriptively and qualitatively. Data collection techniques are carried out through observation, which involves direct field observations of real conditions, and interviews, which involve direct interviews with respondents, informants, or sources. Based on the research findings, it is known that the implementation of Government Regulation No. 43 of 2007 regarding the recruitment of Regional Civil Service Candidates is used as a guideline that must be followed by the Probolinggo Regency Government, the organizing agencies, and related units. However, in practice, conflicts of interest often arise between various parties, both between the organizing agency and the related work units, as well as with honorary staff who are appointed as Regional Civil Service Candidates.